Case report: Advanced modified pneumatic retinopexy for treating simultaneous bilateral rhegmatogenous retinal detachment - Guo, Shenchao; Zhu, Tiepei; Zhang, Xin; Li, Gaochun; Xiang, Zhenyang; Li, Enhui (Frontiers in Medicine, 2024)
Background: Simultaneous bilateral rhegmatogenous retinal detachment (RRD) is a rare and challenging condition in ophthalmology. This case report focuses on a modified pneumatic retinopexy technique, designed to improve treatment outcomes for this difficult condition. Case presentation: A 59-year-old male presented with decreased visual acuity in his right eye for one week. Examination revealed extensive retinal detachment in the right eye with multiple superior breaks and macula off, separated by approximately 3 clock hours. The left eye exhibited one quartile of retinal detachment with superior breaks and macula on. Bilateral simultaneous PR was performed for retinal repair. In the modified PR procedure, 0.7 ml of low-concentration perfluoropropane and 0.7 ml of filtered pure air were intravitreally injected into the right and left eyes, respectively. A head position maneuver was then employed to sequentially close retinal breaks, followed by laser photocoagulation once the surrounding retina reattached. Two days after gas injection, both retinas were completely reattached. Best corrected visual acuity improved to 0.6 in the right eye and 0.9 in the left eye at the 8-month follow-up.The innovative modified pneumatic retinopexy technique presented in this case report offers a promising new approach for effectively treating simultaneous bilateral rhegmatogenous retinal detachment.